2001
DOI: 10.1149/1.1375799
|View full text |Cite
|
Sign up to set email alerts
|

Oxide Dual Damascene Trench Etch Profile Control

Abstract: A systematic study of trench profile evolution in a medium-density oxide etch reactor is presented. A Langmuir site balance model is developed in the limit of unity sticking coefficient which exhibits a flat etch front as is frequently required for dual damascene applications. The model indicates that it is desirable to operate in a neutral-limited ion-assisted etch regime. Physical sputtering is also shown to be necessary, but this etch contribution must be kept small with respect to the ion-assisted etch rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…67 Consequently, the ratio S 0 J n /a ia Y ia J i , which determines whether the etch regime is ion limited or neutral starved, and the maximum physical sputtering rate Y ps J i , which contributes to microtrenching, should both vary with pressure. 56. This behavior is illustrated in Fig.…”
Section: ͑4͒mentioning
confidence: 74%
See 2 more Smart Citations
“…67 Consequently, the ratio S 0 J n /a ia Y ia J i , which determines whether the etch regime is ion limited or neutral starved, and the maximum physical sputtering rate Y ps J i , which contributes to microtrenching, should both vary with pressure. 56. This behavior is illustrated in Fig.…”
Section: ͑4͒mentioning
confidence: 74%
“…Methods for achieving a controlled flat etch front have been identified, 56,57 and can be motivated by appealing to ion-assisted etch models derived from site-balance relationships determined by Langmuir adsorption kinetics. Any departure from this goal can only be in the direction of very slight bottom rounding.…”
Section: Trench-first Trench Etchmentioning
confidence: 99%
See 1 more Smart Citation
“…Microtrenching is caused by ion reflection from the sidewalls of features [48]. Microtrenching is caused by ion reflection from the sidewalls of features [48].…”
Section: Dielectric Patterningmentioning
confidence: 99%
“…It is reported that the reflection characteristic of ions from the sidewall or the charging effect of ions [1][2][3][4][5] mainly causes microtrenches, and that microtrenches are caused by the deposition effect of fluorocarbons formed in the etching gas under high pressure, and the reflection characteristic of ions from the bottom of the trench under low pressure. [6][7][8][9] These reports are based on experimental results and a common mechanism for microtrench generation has not been established yet. Moreover, although the trench etching process in the SiO 2 layer has been simulated, the mechanism of microtrench generation has not been considered.…”
Section: Introductionmentioning
confidence: 99%